Quality evaluation of ultrasound imaging in the carotid artery - Loizou, Christos P.; Pattichis, Constantinos S.; Istepanian, Robert S H; Pantziaris, Marios; Tyllis, Theodosis H.; Nicolaides, Andrew N. (My University, 2004)
Image quality assessment plays an important role in various image-processing applications. In this work we evaluate image quality criteria based on mean square error, signal to noise error, and quality and structural similarity indices on ultrasound imaging of the carotid artery. These criteria as well as statistical and texture features were computed on 80 images recorded from two different ultrasound scanners before and after despeckle filtering, and after despeckle filtering and normalization. Results showed that image quality was improved after despeckle filtering and normalization for both scanners. This finding is also in agreement with the optical perception evaluation carried out by two vascular experts.
Keywords: Image quality; De-speckle filtering; Biomedical optical imaging; Ultrasonic imaging; Carotid arteries; Optical filters; Degradation